Green marketing orientation impact on business performance: Case of pharmaceutical industry of Pakistan - Shaukat, Fatima; Ming, Jia (Frontiers in Psychology, 2022)
This study is based on the natural resource based view, which examines the impact of holistic marketing orientation on business performance (BP) by defining the role of enablers and mediators. The drivers, including corporate social responsibility (CSR) and environmental culture (EC) influence, are tested by analyzing the role of sustainable competitive advantage (SCA) as a mediator. The analysis is based on 298 samples collected from top and middle-level managers working in the pharmaceutical industry. Structural equation modeling was undertaken using Smart PLS 3.2.8. The research outcomes reveal that corporate social responsibility and environmental culture have a substantial impact on green marketing orientation (GMO). The results show that GMO has a significant direct and indirect impact on business performance while a full mediation of sustainable competitive advantage exists between the green marketing orientation and business performance. The outcomes will facilitate managers in green marketing strategy and decision making in the long-term, with 3-fold benefits in addition to strengthening their competitiveness.